2003
DOI: 10.1063/1.1619562
|View full text |Cite
|
Sign up to set email alerts
|

Large anomalous enhancement of perpendicular exchange bias by introduction of a nonmagnetic spacer between the ferromagnetic and antiferromagnetic layers

Abstract: In (Pt/Co)n/FeMn multilayers, the magnitude of exchange bias, HE, can be considerably enhanced by placing an ultrathin nonmagnetic Pt spacer between the multilayer (ML) and the antiferromagnetic (AFM) layer. The bias is maximum for a spacer layer thickness, t, of a few angstroms and it decreases progressively as t is further increased. This bias enhancement is accompanied by an increase of coercivity, HC. This behavior is due to the role of the Pt spacer in enhancing the perpendicular effective anisotropy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 24 publications
6
84
0
Order By: Relevance
“…19 It has recently been shown that the exchange bias of Co/ Pt multilayers with out-of-plane magnetization can be enhanced by the insertion of a thin Pt layer at the Co/ AFM interface. 15,19 Figure 4 shows that this also holds for our IrMn exchange-biased structures. For SiO 2 / ͓Pt ͑20 Å͒ / Co ͑5 Å͔͒ 3 /Pt ͑t Å͒ / IrMn ͑100 Å͒ /Pt ͑20 Å͒ multilayers the perpendicular exchange bias initially increases and then decreases with the Pt insertion layer thickness.…”
Section: Journal Of Applied Physicsmentioning
confidence: 61%
See 1 more Smart Citation
“…19 It has recently been shown that the exchange bias of Co/ Pt multilayers with out-of-plane magnetization can be enhanced by the insertion of a thin Pt layer at the Co/ AFM interface. 15,19 Figure 4 shows that this also holds for our IrMn exchange-biased structures. For SiO 2 / ͓Pt ͑20 Å͒ / Co ͑5 Å͔͒ 3 /Pt ͑t Å͒ / IrMn ͑100 Å͒ /Pt ͑20 Å͒ multilayers the perpendicular exchange bias initially increases and then decreases with the Pt insertion layer thickness.…”
Section: Journal Of Applied Physicsmentioning
confidence: 61%
“…[2][3][4][5][6][7] Although it has been intensively studied for systems with in-plane magnetization, it has hardly been used in recent studies on perpendicular exchange bias. [8][9][10][11][12][13][14][15][16][17][18] In a recent paper, Sort et al showed that Co/ Pt multilayers with out-ofplane magnetization can be biased by growing an IrMn layer on top. 19 In this paper we present an overview on the exchange-biasing properties of IrMn in systems with perpendicular magnetic anisotropy.…”
mentioning
confidence: 99%
“…They showed that the exchange bias field of Co/ Pt-FeMn and Co/ Pt-IrMn systems is enhanced by the insertion of a thin Pt film between the Co and the AFM layer. 12,23 It was argued that the Pt reorients the Co spins from a tilted position ͑due the in-plane anisotropy of the Co/ AFM interface͒ towards the film normal, leading to a larger perpendicular exchange bias. We measured a similar enhancement of the exchange bias field in SiO 2 / ͓Pt ͑20 Å͒ /Co ͑5 Å͔͒ 3 /Pt͑t͒ / IrMn ͑100 Å͒ /Pt ͑20 Å͒ multilayers.…”
Section: Discussionmentioning
confidence: 99%
“…Among them are Co/ Pt multilayers with CoO ͑Refs. 4-7͒ and NiO, 8 Co/ Pt, CoFe/ Pt, Co/ Pd, and FeNi/ FeMn multilayers with FeMn, [9][10][11][12][13][14][15] and NiFe/ CoO multilayers. 16 Although these systems are interesting for fundamental studies of the exchange bias phenomenon, the low blocking temperature of CoO and NiO and the low corrosion resistance of FeMn limit their application potential.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, F. Garcia, J. Sort and co-workers observed significant enhancement of the bias after insertion of a very thin nonmagnetic spacer at the FM/AFM interface in the (Pt/Co 0.9 Fe 0.1 ) n /NM/(Co 0.9 Fe 0.1 /Pt) m /Co 0.9 Fe 0.1 /FeMn (NM=Cu, Pt) systems [10,11]. This phenomenon can be called an "imprint effect," as the nonmagnetic spacer significantly modifies the natural interface morphology, influencing the coupling between FM and AFM spins that are perpendicular to plane.…”
Section: Introductionmentioning
confidence: 99%